The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/plants12010088
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Regulators of the Onset and End of the Seed Release Phenology of a Temperate Desert Shrub Nitraria tangutorum

Abstract: Seed release is crucial in the reproductive cycle of many desert plant species, but their responses to precipitation changes are still unclear. To clarify the response patterns, we conducted a long-term in situ water addition experiment with five treatments, including natural precipitation (control) plus an extra 25%, 50%, 75%, and 100% of the local mean annual precipitation (145 mm), in a temperate desert in northwestern China. Both the onset and end of the seed release phenophase of the locally dominant shru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Nitraria tangutorum is the predominant plant class in the Ulan Buh Desert [ 46 , 55 , 56 ], and its leaves had a high storage capacity for C and N [ 51 ]. Previous studies have shown that growth and biomass production of plant was accelerated by N application [ 57 ] but was inhibited when the N supply was excessive [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nitraria tangutorum is the predominant plant class in the Ulan Buh Desert [ 46 , 55 , 56 ], and its leaves had a high storage capacity for C and N [ 51 ]. Previous studies have shown that growth and biomass production of plant was accelerated by N application [ 57 ] but was inhibited when the N supply was excessive [ 24 ].…”
Section: Discussionmentioning
confidence: 99%